Pemberdayaan Masyarakat Melalui Pelatihan Pemasaran Digital Marketing dan Fotografi PKK Padukuhan Karanglo Sedayu Bantul - Asrima, Nuri Pari Julia; Nabila, Silvi; Karindra, Evrilya Deby; Wulan, Nawang; Febrianto, Faisal; Listiyani, Arfina; Andiyansari, Popi; Ahmad, Entus Nuryana; Ahmad, Syukron; Dalili, Dalili (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
This activity, which is part of the Community Empowerment Communication (KPM) program, aims to improve the ability of PKK members who have MSME products to market their products through "Digital Marketing and Photography". The problems experienced by PKK members are the lack of understanding of Micro, Small and Medium Enterprises (MSMEs) in Argomulyo Sedayu to promote their products using social media by displaying good and attractive product photos, and the background of the partner members is heterogeneous so knowledge is needed in taking photos and editing product photos with a smartphone camera. The implementation method used is face-to-face training through preparation stages such as surveying activity locations, and the implementation stage which includes training in using smartphones for product photography and photo editing for making product advertisements for members of the PKK Karanglo Argomulyo Sedayu Bantul Yogyakarta, stage monitoring and evaluation to see the effectiveness and response of participants. The results obtained from the presentation of material, training and practice have broadened the participants' insight into the use of Digital Marketing on Smartphones for product photos to create advertisements and product marketing for members of PKK Karanglo, Argomulyo Sedayu, Bantul, Yogyakarta.